2016
DOI: 10.1186/s13756-016-0159-7
|View full text |Cite
|
Sign up to set email alerts
|

“If it’s a broad spectrum, it can shoot better”: inappropriate antibiotic prescribing in Cambodia

Abstract: BackgroundCambodia is affected by antibiotic resistance but interventions to reduce the level of resistance require knowledge of the phenomena that lead to inappropriate prescribing. We interviewed physicians working in public hospitals to explore the drivers of inappropriate antibiotic prescribing.MethodsHospitals participating in a knowledge, attitudes and practices survey prior to this study were purposively selected and physicians were randomly recruited to participate in focus group discussions. Nvivo ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 26 publications
4
46
0
Order By: Relevance
“…For example, at the time of this manuscript’s preparation, Takeo Provincial Referral Hospital’s annual allotment of formulary antimicrobials included enough ceftazidime to properly treat only 12–14 melioidosis patients. Additionally, a recent survey revealed that only 17% of Cambodian physicians have any experience treating melioidosis [ 56 ]. Although numbers are too small to draw significant statistical conclusions from our series, it is interesting to note that of the four patients who survived long enough to receive a course of ceftazidime or meropenem, three survived.…”
Section: Discussionmentioning
confidence: 99%
“…For example, at the time of this manuscript’s preparation, Takeo Provincial Referral Hospital’s annual allotment of formulary antimicrobials included enough ceftazidime to properly treat only 12–14 melioidosis patients. Additionally, a recent survey revealed that only 17% of Cambodian physicians have any experience treating melioidosis [ 56 ]. Although numbers are too small to draw significant statistical conclusions from our series, it is interesting to note that of the four patients who survived long enough to receive a course of ceftazidime or meropenem, three survived.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our findings suggest that amphenicol resistance genes are circulating in the community, potentially because amphenicol use in food animals has selected for resistant bacteria that can spread to humans ( 12 ). This possibility is concerning because physicians in Cambodia are often unable to assess the resistance of infectious agents before prescribing antimicrobial drugs ( 4 ). …”
Section: The Studymentioning
confidence: 99%
“…Few studies have been conducted in low- and middle-income countries, where colonization rates can exceed 60% ( 2 ). High ESBL colonization rates in low- and middle-income countries such as Cambodia are usually attributed to unrestricted consumer access to and hospital overuse of third-generation cephalosporins ( 3 , 4 ). However, antimicrobial drugs in classes critical for human health (e.g., β-lactams, macrolides, aminoglycosides, polymyxins) are increasingly being used in food animals ( 5 ).…”
mentioning
confidence: 99%
“…7 Factors such as patients' demands, doctors' personal experiences and preferences, lack of culture and sensitivity results leading to uncertain diagnosis, sale of antibiotics without prescription are some of the most common contributors towards antibiotic resistance, poor knowledge and lack of knowledge on rational prescribing and AMR. 8,9 Knowledge and beliefs influence health-related behavior with regards to using antibiotics. 10 Inappropriate attitudes and lack of knowledge towards the use of antibiotics is a high-risk factor contributing to the rise of AMR cases.…”
Section: Introductionmentioning
confidence: 99%